PERHITUNGAN TARIF JASA PENGINAPAN DENGAN METODE ACTIVITY BASED COSTING (STUDI KASUS PADA HOTEL ARUNA SENGGIGI) - Supraptik Supraptik (JURNAL KOMPETITIF : MEDIA INFORMASI EKONOMI PEMBANGUNAN, MANAJEMEN DAN AKUNTANSI, 2022)
This research is entitled "Calculation of Lodging Service Rates With Activity Based Costing Method" (Case Study at Aruna Senggigi Hotel). The purpose of this study is to analyze the application of the calculation of lodging service rates at the Aruna Senggigi Hotel, using the Activity Based Costing System method and to analyze the determination of the lodging service rates at the Aruna Senggigi Hotel, which can be applied using the Activity Based Costing System method. This type of research is using comparative descriptive. The results show that the calculation of lodging service rates at the Aruna Senggigi hotel can be applied using the Activity Based Costing system method, but for the superior cottage and deluxe cottage classes it cannot be applied using the Activity Based Costing system method because the tariff for lodging services after using the Activity Based Costing system becomes more expensive. larger than traditional methods. Calculation of lodging service rates using the Activity Based Costing system approach, is carried out in several stages. That is, firstly, costs are traced to activities that incur costs and the next stage is to assign activity costs to products. Meanwhile, the rate is obtained by increasing the cost of lodging with the expected profit of the hotel. The use of the Activity Based Costing system method in calculating the tariff for lodging services will result in an accurate calculation of service rates, because the costs incurred are charged to the product on the basis of the activities and resources consumed by the product and also uses the basis of more than one cost driver. Determination of lodging service rates using the Activity Based Costing system method can be applied to the Aruna Senggigi hotel because the service rates using the Activity Based Costing system method are smaller than the traditional method.